Exploring Reliability and Validity for the Professional Quality of Life Scale - McClure, Caitlyn; Anderson, Jennifer June (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
The Professional Quality of Life (ProQOL) instrument has been in use in some variation for decades with the most recent iteration becoming available in 2009. With twelve years of changes in the workforce plus applications of the ProQOL in novel professional groups, it is critical to determine if the tool is still reliable and valid. Data obtained from specific occupational groups, specifically college resident assistants (RAs) and substance abuse professionals (SAPs), will be utilized to explore if the measure holds up to past research claiming high reliability and validity. It is possible that the RAs (n=358) and the SAPs (n=40) will be outliers from these claims due to their unique positionality in their roles or due to the amount of time that has passed since the last update of the ProQOL.